1986
DOI: 10.1021/i300023a021
|View full text |Cite
|
Sign up to set email alerts
|

Hydroisomerization and hydrocracking of n-alkanes. 1. Ideal hydroisomerization PtHY catalysts

Abstract: The transformation of n-heptane was studied at 250 °C, 1 atm, and PH/Pn-heptane = 9 on a series of PtHY catalysts containing from 0.1 to 1.5 wt % platinum and having Si/AI atomic ratios of 3, 9, or 35. The activities, stabilities, and selectivities of the catalysts are clearly governed by the number of their acid sites (nA) and hydrogenating sites (np,). nA is defined here as the number of acid sites on which the adsorption heat of NH3 is greater than 100 kj mol"1 and zip, as the number of accessible platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(74 citation statements)
references
References 3 publications
6
68
0
Order By: Relevance
“…It yields an n-C 4 /C 3 instead of an i-C 4 /C 3 product pair (28,(37)(38)(39). It occurs when there are multiple transformations at acid sites inside pores that significantly limit sorbate mobility (14,28,38,40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It yields an n-C 4 /C 3 instead of an i-C 4 /C 3 product pair (28,(37)(38)(39). It occurs when there are multiple transformations at acid sites inside pores that significantly limit sorbate mobility (14,28,38,40).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that n-C 7 and n-C 10 share essentially the same hydroconversion mechanism (37,39,44,45,46). The only difference between n-C 7 and n-C 10 is that the latter can hydroisomerize into a tribranched "iii-C 10 " isomer with both geminal and quasi-vicinal methyl groups (i.e., with methyl groups on α,α,γ positions) (39, 44-48) before hydrocracking, whereas the former is too short to form the equivalent iii-C 7 hydrocracking precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…n-Heptane was the selected starting feedstock for all processes as widely used in literature [26][27][28] and more reactive raw material as compared to n-hexane or n-pentane [29]. This compound is also present in the gasoline fraction.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…16,18 Furthermore, the degree of noble metal dispersion, interplay between hydrogenation/dehydrogenation and acidic sites, and spatial constraints within zeolitic micropores were demonstrated to affect isomerization activity and selectivity. 16,[19][20][21] Even though hydroisomerization process has been extensively studied for decades, there is a need for highly selective catalyst, especially at high temperature conditions. In industrial hydrocarbon conversion settings, high temperature conditions are favored to increase the overall turnover rate of the reactions.…”
Section: Introductionmentioning
confidence: 99%